INTERDISCIPLINARY INTEGRATION AS THE FACTOR IN IMPROVING THE QUALITY OF EDUCATION - Eshto'xtarova, Orzigul (Физико-технологического образование, 2021)
In this paper, the problem of interdisciplinary integration in the educational system is investigated. It was shown that interdisciplinary integration is presented as a means of increasing students' independent creative abilities, increasing and shaping their worldview and scientific thinking, and ultimately improving the entire educational process